Racial/Ethnic Disparities in US Pediatric Growth Hormone Treatment - Grimberg, Adda; Lindberg, Anders; Wajnrajch, Michael; Cucchiara, Andrew J; Camacho-Hübner, Cecilia (Hormone research in paediatrics, 2018)
To compare racial/ethnic proportions of subjects receiving growth hormone (GH) treatment to the expected proportions, and secondarily, to assess racial/ethnic differences in subject characteristics at GH treatment initiation. Race/ethnicity-based expected frequencies of height <-2.25 SD were determined by applying relative risks for short stature, calculated from a regional population of 189,280 pediatric primary care patients, to US census data, and compared to racial/ethnic proportions of US subjects enrolled in the Pfizer International Growth Study (KIGS) using the χ2 test. Characteristics of white and black subjects at GH treatment initiation were presented as medians and compared by the Wilcoxon rank sum test (significant p < 0.01). White subjects exceeded the expected frequency (63%) for all indications (83%) and each separately, ranging from 73% for congenital GH deficiency (GHD) to 85% for idiopathic short stature (p < 0.001). Compared to white subjects, black subjects treated for idiopathic GHD had greater height deficits relative both to the population (-2.97 vs. -2.56 SD) and to their mid-parental heights (-2.47 vs. -1.89 SD), lower stimulated GH peak levels (4.9 vs. 6.0 ng/mL), and lower birth weights (-0.86 vs. -0.48 SD). Black subjects with congenital GHD had lower stimulated GH peaks (2.1 vs. 3.2 ng/mL) and started GH treatment at younger ages (2.9 vs. 4.8 years), while those with acquired GHD had lower birth weights (-1.12 vs. -0.08 SD). Male predominance did not differ by race for any or all indications. Overrepresentation of white children among those receiving GH treatment in the US KIGS registry reflects racial/ethnic treatment biases, not just differences in growth rates.